Botulinum toxin type A affects the transcriptome of cell cultures derived from muscle biopsies of controls and spastic patients. (August 2018) - Zanotti, Simona; Kapetis, Dimos; Gibertini, Sara; Salerno, Franco; Ciusani, Emilio; Colombo, Chiara; Gronchi, Alessandro; Morandi, Lucia; Mantegazza, Renato; Molteni, Franco; Mora, Marina
Abstract: Botulin toxin (BTX) is widely used for treating skeletal muscle spasticity. Experimental reports on BTX treatment were mainly focused on the neuromuscular junction, while relatively little is known about toxin effects on the muscle cell itself. We investigated possible impact of BTX type A on skeletal muscle cell transcriptome by microarray analysis in muscle-derived cell cultures (fibroblasts, myoblasts and myotubes) from controls and spastic patients, and results were then validated at transcript and protein level. BTX-A treatment of control cells induced major changes in the myogenic component of the transcriptome, whereas the same treatment had a negligible effect in the fibrogenic component. BTX-A treatment of cell cultures from spastic patients induced an increased number of genes differentially expressed both in the fibrogenic and myogenic components. Specifically, BTX-A had a major effect on cell cycle-related genes in myoblasts, on muscle contraction-related genes in myotubes, and on extracellular matrix-related genes in fibroblasts from spastic patients. Our findings show that in vitro BTX-A treatment differentially affects transcript expression in muscle cells from spastic patients compared to those from controls suggesting a direct effect of BTX-A on muscle-specific functional pathways. Highlights: Botulinum toxin (BTX-A) treatment induced major changes in muscle-derived cell transcriptome. Changes were greater in the myogenic and negligible in the fibrogenic components of control cells. BTX-A modified more genes in muscle-derived cells from spastic patients than in control cells.